Hospital Change Management in the Digital Era: A Systematic Literature Review of Leadership, Ambidexterity, and Innovation - Yulivitri Yulivitri; Purwanto Purwanto (Yayasan Riset dan Pengembangan Intelektual, 2026)
Purpose: Hospitals are undergoing digital transformation through electronic health records, telemedicine, virtual care, artificial intelligence, patient portals, and data-driven operations. Yet the implementation of these technologies frequently produces organizational tensions that cannot be explained by technology-adoption logic alone. This systematic literature review examines hospital change management in the digital era by integrating evidence on leadership, ambidexterity, and innovation. Design/methodology/approach: The review followed the SPAR-4-SLR logic of assembling, arranging, and assessing the literature and used a PRISMA-informed screening flow. The evidence boundary was deliberately restricted to Scopus-confirmed Q1/Q2 journal articles. From 1,343 raw records, 1,323 unique records were retained after deduplication. After source-quality, document-type, and topical screening, 175 articles were included in qualitative synthesis. Findings: The review identifies five interrelated patterns. First, hospital digital change is a sociotechnical process that reshapes workflow, accountability, professional identity, and care coordination. Second, readiness is multidimensional, combining digital competence, technological self-efficacy, managerial capability, psychological safety, and learning climate. Third, leadership operates as a translation mechanism between executive digital strategy and frontline clinical practice. Fourth, ambidexterity provides a strategic explanation for how hospitals balance reliability, standardization, and safety with experimentation and innovation. Fifth, innovative work behaviour is a proximal behavioural pathway through which digital change becomes embedded in practice. Originality/value: The review develops a paradox-informed digital leadership framework for hospital change management. It contributes by connecting hospital digital transformation, paradoxical leadership, digital leadership, ambidexterity, and innovative work behaviour into a coherent agenda for future empirical research.